Adiposity and metabolic health in Asian populations: an epidemiological study using dual-energy x-ray absorptiometry in Singapore - Mina, Theresia (2024)
Type 2 diabetes, cardiovascular disease, and related cardiometabolic disturbances are increasing rapidly in the Asia-Pacific region. We investigated the contribution of excess adiposity, a key determinant of type 2 diabetes and cardiovascular risk, to unfavourable cardiometabolic profiles among Asian ethnic subgroups. The Health for Life in Singapore (HELIOS) Study is a population-based cohort comprising multiethnic Asian men and women living in Singapore, aged 30–84 years. We performed a cross-sectional analysis of data from individuals who had assessment of body composition by dual-energy x-ray absorptiometry and metabolic characterisation. In a subset of participants on no medication for type 2 diabetes, hypertension, and hypercholesterolaemia, we tested the relationship of BMI and visceral fat mass index (vFMI) with cardiometabolic phenotypes (glycaemic indices, lipid levels, and blood pressure), disease outcomes (type 2 diabetes, hypercholesterolaemia, and hypertension), and metabolic syndrome score with multivariable regression analyses. Between April 2, 2018, and Jan 28, 2022, 10 004 individuals consented to be part of the HELIOS cohort, of whom 9067 were included in the study (5404 [59·6%] female, 3663 [40·4%] male; 6224 [68·6%] Chinese, 1169 [12·9%] Malay, 1674 [18·5%] Indian; mean age 52·8 years [SD 11·8]). The prevalence of type 2 diabetes, hypercholesterolaemia, and hypertension was 8·2% (n=744), 27·2% (n=2469), and 18·0% (n=1630), respectively. Malay and Indian participants had 3–4-times higher odds of obesity and type 2 diabetes, and showed adverse metabolic and adiposity profiles, compared with Chinese participants. Excess adiposity was associated with adverse cardiometabolic health indices including type 2 diabetes (p<0·0001). However, while vFMI explained the differences in triglycerides and blood pressure between the Asian ethnic groups, increased vFMI did not explain higher glucose levels, reduced insulin sensitivity, and increased risk of type 2 diabetes among Indian participants. Visceral adiposity is an independent risk factor for metabolic disease in Asian populations, and accounts for a large fraction of type 2 diabetes cases in each of the ethnic groups studied. However, the variation in insulin resistance and type 2 diabetes risk between Asian subgroups is not consistently explained by adiposity, indicating an important role for additional mechanisms underlying the susceptibility to cardiometabolic disease in Asian populations.